An exome-wide study of renal operational tolerance - Massart, Annick; Danger, Richard; Olsen, Catharina; Emond, Mary J.; Viklicky, Ondrej; Jacquemin, Valérie; Soblet, Julie; Duerinckx, Sarah; Croes, Didier; Perazzolo, Camille; Hruba, Petra; Daneels, Dorien; et al. (Frontiers in Medicine, 2023)
Background. Renal operational tolerance is a rare and beneficial state of prolonged renal allograft function in the absence of immunosuppression. The underlying mechanisms are unknown. We hypothesized that tolerance might be driven by inherited protein coding genetic variants with large effect, at least in some patients. Methods. We set up a European survey of over 218,000 renal transplant recipients and collected DNAs from 40 transplant recipients who maintained good allograft function without immunosuppression for at least one year. We performed an exome-wide association study comparing the distribution of moderate to high impact variants in 36 tolerant patients, selected for genetic homogeneity using principal component analysis, and 192 controls, using an optimal sequence-kernel association test adjusted for small samples. Results. We identified rare variants of HOMER2 (3/36, FDR 0.0387), IQCH (5/36, FDR 0.0362), and LCN2 (3/36, FDR 0.102) in 10 tolerant patients vs 0 controls. One patient carried a variant in both HOMER2 and LCN2. Furthermore, the three genes showed an identical variant in two patients each. The three genes are expressed at the primary cilium, a key structure in immune responses. Conclusion. Rare protein coding variants in a small set of primary cilium genes are associated with operational tolerance in a sizable portion of patients. Our findings have important implications for a better understanding of immune tolerance in transplantation and other fields of medicine.ClinicalTrials.gov Identifier NCT05124444.